Pengaruh Karir dan Kemandirian Ekonomi terhadap Keterlambatan Pernikahan Wanita Dewasa Awal: (Studi Kasus di Medan Sumatera Utara) - Nurhasana Nurhasana; Lalu Amirudin; Risa Susanti; M. Zidny Nafi' Hasbi (Jurnal Budi Pekerti Agama Islam, 2026)
This study explores the influence of career factors and economic independence on the phenomenon of late marriage in early adult women (aged 25-35 years) in Indonesia, especially in urban areas of North Sumatra such as Medan. Adopting a mixed-methods design, the study involved a quantitative survey of 250 career female respondents (with age criteria above 25 years old, unmarried, and a minimum income of the city UMR) using the Likert scale to measure career priorities as well as the financial independence index, complemented by logistic regression analysis to test causal relationships. Semi-structural interviews with 20 key informants uncovered an in-depth narrative about the trade-offs between professional ambitions (such as job promotion and income stability) and traditional marriage expectations. Key findings show that women with a bachelor's degree and above and an income of 1.5 times UMR tend to postpone marriage until the average age of 31.4 years, driven by the desire to achieve economic independence (regression coefficient β=0.42, p<0.01) as well as the flexibility of living without partner dependence. However, moderator factors such as Batak or Malay cultural pressures in Medan create internal conflicts, with 68% of respondents reporting social stress from family. Theoretically, the results support role conflict theory in modern family dynamics, while implications include recommendations for work-life balance-based pre-marital counseling programs and corporate policies to support high-quality marriages. This research contributes to the Indonesian family relations literature by highlighting the paradigm shift from patriarchal norms towards gender equality.